2022
DOI: 10.1021/acssuschemeng.2c04695
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glycerol in Preserving Proteins Needs to Be Reconsidered

Abstract: The safe and efficient stabilization and preservation of enzymes, therapeutic proteins, and biomaterials are increasingly important in biology, medicine, and pharmaceutics. Various protectants have been explored, but their protective actions on protein structures remain unclear. Herein, we present an all-around protectant–protein interaction landscape by investigating the behaviors of Bacillus subtilis lipase A (BSLA), cellobiohydrolase I from Trichoderma reesei (CBHI), and endoglucanase from Penicillium Verru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…The computational study, especially molecular dynamics (MD) simulation, can provide a molecular understanding of the identified enzymes 43,[51][52][53][54][55] . Towards in silico characterization of Phase III, the predicted 3D structure of ChryBHETase by AlphaFold2 lacked two regions (residues 251-272 and 245-369) compared to BsEst and TfCa, as shown in sequence alignment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The computational study, especially molecular dynamics (MD) simulation, can provide a molecular understanding of the identified enzymes 43,[51][52][53][54][55] . Towards in silico characterization of Phase III, the predicted 3D structure of ChryBHETase by AlphaFold2 lacked two regions (residues 251-272 and 245-369) compared to BsEst and TfCa, as shown in sequence alignment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important that it should confer stability and maintain the enzyme activity. It has been reported that enzymes can remain stable and active in non-aqueous solvents, such as glycerol, but this is not applicable to all classes of enzymes [ 9 , 10 , 11 ]. Other alternatives have been searched, namely the use of deep eutectic systems (DESs) [ 12 , 13 ].…”
Section: Deep Eutectic Systemsmentioning
confidence: 99%
“…[3] However, recent reports indicate that the stabilizing effect is not universally applicable to all class of enzymes. [4] Various methodologies reporting the use of non-conventional media for biocatalyzed processes have been extensively reviewed. [5] Deep Eutectic Solvents (DESs) are eutectic mixtures commonly obtained by mixing, heating and stirring a hydrogen bond acceptor (HBA) and a hydrogen bond donor (HBD) in specific molar ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Among hydrophilic solvents, glycerol can mimic the effect of water and is reported to preserve enzyme structure [3] . However, recent reports indicate that the stabilizing effect is not universally applicable to all class of enzymes [4] . Various methodologies reporting the use of non‐conventional media for biocatalyzed processes have been extensively reviewed [5] .…”
Section: Introductionmentioning
confidence: 99%